Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.4018/ijsesd.2021100105
|View full text |Cite
|
Sign up to set email alerts
|

Creating Sustainable Agriculture Supply Chain Ecosystem for Remunerative Markets Under Changing Climate in Uttarakhand

Abstract: Major issues in the sustainable development agenda include how to ensure the involvement of producers. Little research has been done of the agricultural supply chain to identify what adaptive measures are being considered or have already been taken for creating remunerative markets. Based on discussions with producers, processors, and retailers from Uttarakhand and nearby regions, this study examines to what extent the Uttarakhand agricultural supply chain ecosystem can sustain and transform with climate chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Natural conservation and financial access were determinants for farmers to adopt sustainable techniques (Kopytko, 2019). Remunerative markets (agritourism, contract farming, and integrated food processing) can help support farmers' financial sustainability (Trivedi and Sunder, 2021). Singh et al (2021) found that flood-recession farming can upscale community livelihood and food security and improve environmental conditions near the river.…”
Section: Farmers In Developing Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural conservation and financial access were determinants for farmers to adopt sustainable techniques (Kopytko, 2019). Remunerative markets (agritourism, contract farming, and integrated food processing) can help support farmers' financial sustainability (Trivedi and Sunder, 2021). Singh et al (2021) found that flood-recession farming can upscale community livelihood and food security and improve environmental conditions near the river.…”
Section: Farmers In Developing Countriesmentioning
confidence: 99%
“…Practices such as using organic fertilizer and intercropping maize and legumes (Maggio, Mastrorillo and Sitko, 2022) and combining mulching and irrigation with farming activities can help farmers adapt to CC (Byrareddy et al, 2021). Remunerative markets, such as agritourism or contract farming, and the rice-fish farming system can generate high farm income and productivity, hence providing farmers with financial sustainability (Bosma et al, 2012;Trivedi and Sunder, 2021). Moreover, agroecology or flood recession farming can also provide such benefits while mitigating CC and improving environmental conditions (Rakotovao et al, 2021;Singh et al, 2021).…”
Section: Challenges In Implementing Circular Economy and Sustainable ...mentioning
confidence: 99%